Tunable optofluidic aperture configured by a liquid-core/liquid-cladding structure - Song, Chaolong (2012)
Miniaturized and tunable optical components, such as the waveguide, lens, and prism, have been of great interest for lab-on-chip systems. This Letter reports an optofluidic aperture stop formed by the liquid-core/liquid-cladding flow. The aperture size can be tuned accordingly by adjusting the flow rates. Manipulation of the aperture size allows control of the amount of light passing through the corresponding optical system as well as the angular aperture on the image side. This optofluidic aperture enables lab-on-chip optical systems to have a greater flexibility and more functionalities.